Test Control of Inclusive Physical Education: Assessment Using the Newest Electronics - Blavt, Oksana; Iedynak, Gennadii; Galamanzhuk, Lesia; Zhygulova, Evelinа; Mykhalskа, Yulia; Khomych, Anatolii; Sovtysik, Dmytro (Physical Education Theory and Methodology, 2023)
The purpose of the study was to determine the effectiveness of a device developed based on the latest electronics to control the coordination of movements of the lower limbs of students with disabilities. Materials and methods. 34 students with disabilities were involved in the study. At the time of the experiment, they had functional disorders of the lower limbs as a result of injuries and received a doctor’s permission to participate in the experiment. The research was conducted at the theoretical and empirical levels, using the following methods: analysis, synthesis, systematization, generalization, technical modeling, pedagogical testing, and mathematical statistics. Results. In the research process, a device was used, which was developed as part of the conducted research. The device consists of two rubber mats in which capacitive proximity sensors are placed. The test task involves recording the number of touches of rubber mats in 20 seconds. The information received from the sensors during the student’s performance of the test task, namely the alternate touching of the rubber mat with the big toe, is sent to the microcontroller via an infrared communication line. The development uses a high-performance microcontroller ATMega 328P, which can support a wide range of sensors and generate information about the time and frequency of leg movements. The signals of the student’s toes touching the rubber mats, received by capacitive sensors, are processed by a microcontroller and displayed on a PC through a serial connection and using the Arduino software, which allows reading the received information about the execution of movements. Under the conditions of the pedagogical experiment, we tried to determine the quality of the measurement results. According to the obtained numerical indicators, the numerical values of the test authenticity obtained by the traditional method of fixing the results by a specialist correspond to the value “low”. The results of the validity calculations showed that the correlation between the test measurement results and the evaluation results using the developed device was optimal with a correlation coefficient greater than 0.6. Conclusions. The importance of a high level of development of the coordination of movements of the lower limbs of students with disabilities is determined by the need to develop this quality to ensure the effectiveness of their rehabilitation in the process of inclusive PE. The analysis of the obtained material allows us to state that the practical application of the inclusive PE device developed based on the latest electronics will allow scientifically based optimization of this process to ensure its effectiveness.